Pembuatan Website Company Profile Untuk PT.Galangan Lautan Lestari Niaga - Irfansyah; Ardiansyah, Muhammad (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2024)
PT.Galangan Lautan Lestari Niaga is a shipyard company that focuses on the construction and repair of barges, tugboats, and oil tankers. It also provides services to private shipping companies. For website development companies, the main challenge in creating a company profile website for PT.Galangan Lautan Lestari Niaga is the approach to the public and the wider recognition of the company's identity. Therefore, this company profile website was created to enhance the value and dissemination of this PT to the public.